2016
DOI: 10.21746/aps.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of essential oils derived from some plants against phytopathogenic fungi

Abstract: Essential oils were extracted from different plant species (Acorus calamus, Artemisia nilagerica, Erigeron Canadensis) to evaluate their effect on the growth of four phytopathogenic fungi viz. Alternaria alternata, Botrytis cinerea, Fusarium oxysporum and Penicillium expansum following poisoned food technique method. Different concentration of oil such as 125ppm, 250ppm, 500ppm, 1000ppm and 5000ppm were taken to evaluate the effect. There was 100% inhibition in the growth of phytopathogenic fungi at 5000 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…However, disease management of this pathogen is still poorly understood, particularly after the application of biological agents. Several previous studies have indicated that the essential oils of A. calamus are effective in inhibiting fungal pathogens, both in humans and plants (Radušienė and Pečiulytė, 2008;Sharma et al, 2009;Yami and Shukla, 2016;Rita et al, 2017). Accordingly, our results indicated that A. calamus essential oil inhibited the growth of C. reteaudii, which causes leaf and shoot blight in Eucalyptus.…”
Section: Discussionsupporting
confidence: 63%
“…However, disease management of this pathogen is still poorly understood, particularly after the application of biological agents. Several previous studies have indicated that the essential oils of A. calamus are effective in inhibiting fungal pathogens, both in humans and plants (Radušienė and Pečiulytė, 2008;Sharma et al, 2009;Yami and Shukla, 2016;Rita et al, 2017). Accordingly, our results indicated that A. calamus essential oil inhibited the growth of C. reteaudii, which causes leaf and shoot blight in Eucalyptus.…”
Section: Discussionsupporting
confidence: 63%
“…Application of essential oil is a very attractive method for controlling postharvest diseases (Hammer et al, 2003;Ahmet et al, 2005). Essential oils and their components are gaining increasing interest because of their relatively safe status, their wide acceptance by consumers, and their exploitation for potential multi-purpose functional use (Yami & Shukla 2016). Essential oils have been used successfully in combination with a variety of treatments, such as antibacterial agents, mild heat and salt compounds (Karatzas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites of plants provide extracts and essential oils with antifungal, antiviral, antibacterial and various other properties. Therefore, they may become active substances for alternative plant disease management (Yami, Shukla, 2016).…”
Section: Introductionmentioning
confidence: 99%